Neural basis of dysphagia in stroke: A systematic review and meta-analysis - Qin, Yin; Tang, Yuting; Liu, Xiaoying; Qiu, Shuting (Frontiers in Human Neuroscience, 2023)
Abstract Objectives: Dysphagia is a major cause of stroke infection and death, and identification of structural and functional brain area changes associated with poststroke dysphagia can help in early screening and clinical intervention. Studies on poststroke dysphagia have reported numerous structural lesions and functional abnormalities in brain regions, and a systematic review is lacking. We aimed to integrate several neuroimaging studies to summarize the empirical evidence of neurological changes leading to poststroke dysphagia. Methods: We conducted a systematic review of studies that used structural neuroimaging and functional neuroimaging approaches to explore structural and functional brain regions associated with swallowing after stroke, with additional evidence using a live likelihood estimation (ALE) approach. Results: A total of 35 studies were included, including 20 studies with structural neuroimaging analysis, 14 studies with functional neuroimaging analysis and one study reporting results for both. The overall results suggest that structural lesions and functional abnormalities in the sensorimotor cortex, insula, cerebellum, cingulate gyrus, thalamus, basal ganglia, and associated white matter connections in individuals with stroke may contribute to swallowing disorders, and the ALE analysis provides additional evidence for structural lesions in the right lentiform nucleus and right thalamus and functional abnormalities in the left thalamus. Conclusion: Our findings suggest that poststroke dysphagia is associated with neurological changes in brain regions such as sensorimotor cortex, insula, cerebellum, cingulate gyrus, thalamus, basal ganglia and associated white matter connections. Adequate understanding of the mechanisms of neural changes in the poststroke swallowing network may assist in clinical diagnosis and provide ideas for the development of new interventions in clinical practice.